2017
DOI: 10.1071/cp16311
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of salinity tolerance in Bromus danthoniae genotypes originated from saline and non-saline areas of West Iran

Abstract: Genetic resources of halophytic grass species are vital factors to be explored for improvement in pasture and rangeland productivity and to elucidate mechanisms of salinity tolerance. The objective of the present study was to understand the adaptive strategies of Bromus danthoniae to a hyper-saline environment by using 80 genotypes originated from saline and non-saline areas in West Iran. Salinity treatments of 0 and 350 mm NaCl were applied for 4 weeks, and plant growth, leaf water status, ionic status, oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…n 43, n 23 and n 27) accumulated much lower Na in the leaves and roots, as compared to those of salinity‐sensitive genotypes (cultivars and a few wild barley genotypes). These findings were consistent with the previous studies on the wild grasses in which the critical role of the sodium (Na) ion in salinity tolerance has been highlighted, particularly at high levels of salinity stress (Arabbeigi et al, ; Hazzouri et al, ; Kiani, Arzani, & Habibi, ; Rezaei et al, ). The effects of the salinity stress on the leaf and root ionic contents also showed that the K concentration and K/Na ratio were significantly decreased under salinity conditions (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…n 43, n 23 and n 27) accumulated much lower Na in the leaves and roots, as compared to those of salinity‐sensitive genotypes (cultivars and a few wild barley genotypes). These findings were consistent with the previous studies on the wild grasses in which the critical role of the sodium (Na) ion in salinity tolerance has been highlighted, particularly at high levels of salinity stress (Arabbeigi et al, ; Hazzouri et al, ; Kiani, Arzani, & Habibi, ; Rezaei et al, ). The effects of the salinity stress on the leaf and root ionic contents also showed that the K concentration and K/Na ratio were significantly decreased under salinity conditions (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, maintenance a high potassium (K) but a low sodium (Na) in the cell cytosol, the synchronized long‐distance transport of Na in the phloem and xylem (Arzani & Ashraf, ) and the Na pumping capacity of root cells across the plasma membrane and then out of the cytosol (Chen et al, ) are the key elements in the salinity tolerance in plants. The significantly higher K/Na ratio observed in the salinity‐tolerant genotypes, as compared to the sensitive ones, is parallel to those reported previously in barley (Hazzouri et al, ; Zhu, Zhou, Shabala, & Shabala, ) and other grasses (Rezaei et al, ). In barley, Zhu et al () noted that better potassium (K) retention along with a reduced cytosol concentration of sodium (Na) in the cells enable optimal K/Na homeostasis in the cytosol which leads to a normal cellular metabolism even under salinity stress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Traits associated with survivability have proved useful in the identification of the most tolerant genotypes to different abiotic stresses, such as salinity (Rezaei et al, 2017 ). Therefore, a weighted selection index was developed in which a 2-folds higher weight was assigned to the survival score.…”
Section: Discussionmentioning
confidence: 99%